HUBUNGAN MOTIVASI BELAJAR DENGAN KEMAMPUAN BERPIKIR TINGKAT TINGGI (HOTS) PADA PEMBELAJARAN IPA SISWA KELAS V SDN 18 SUNGAI TARAB KABUPATEN TANAH DATAR - Nur Alifa, Fauziah; Fitria, Yanti; Ulya Akmal, Atika; Amini, Risda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning motivation may support students’ engagement in complex cognitive activities, yet the higher-order thinking skills (HOTS) of fifth-grade students at SDN 18 Sungai Tarab remained below expectations. This study examined the direction and strength of the association between learning motivation and HOTS in science learning. A quantitative correlational design was applied to 48 students from classes VA and VB, selected purposively from a population of 71 fifth-grade students. Motivation data were obtained through a Likert questionnaire, while HOTS was measured using 15 multiple-choice questions and one essay question covering analysis, evaluation, and creation. The instruments underwent expert review and field testing. Data were processed descriptively and analyzed using Pearson’s product-moment correlation in SPSS 27. The coefficients were 0.453 for class VA, indicating a moderate positive relationship, and 0.918 for class VB, indicating a very strong positive relationship; both outputs were reported at p < 0.05. Teachers’ observations produced an average achievement score of 85.5%, supporting the motivation data. These findings indicate that stronger learning motivation tends to occur alongside better HOTS performance in science learning. The results should be interpreted within the study’s limited, cross-sectional sample.